Teenagers Knowledge On Sexually Transmitted Diseases at SMK Negeri 2 Banjarmasin - Anita Herawati; Ika Mardiatul Ulfa; Septin Hawini (Universitas Sari Mulia, 2018)
Background: Sexually Transmitted Disease is one of the first ten causes of illness in young adult males and the second largest cause of young adulthood of women in developing countries. According to the data of the existing sexually transmitted diseases in the city of Banjarmasin in adolescents classified in large numbers that are in 2014, there are 359 people suffering from PMS and 46 of them tested positive for HIV while 45 of them positive AIDS that 60% of them come from teenagers. In 2015 known 42 people tested positive for HIV while 18 people positive AIDS.Objective: To know the description of adolescent knowledge about the sexually transmitted disease in SMK Negeri 2 Banjarmasin.Method: The research method is a descriptive method. This research was conducted in SMK Negeri 2 Banjarmasin on April 1, 2017, with a sample of teens as much as 81 respondents using sampling technique with proportional random sampling technique and simple random sampling. The instrument used is a standard questionnaire or has been tested for previous research.Result: The result of the research shows that adolescents in class X SMK Negeri 2 Banjarmasin mostly have enough knowledge that is 41 people (50,6%), good knowledge 36 people (44,4%), and knowledge less 4 people (5 %).Conclusion: Knowledge of adolescent about the sexually transmitted disease of class X teenager at SMK Negeri 2 Banjarmasin in enough category.Keywords: Knowledge, Youth, Sexually Transmitted Diseases.